1991
DOI: 10.1055/s-2006-960187
|View full text |Cite
|
Sign up to set email alerts
|

Constituents ofPersicaria stagnina

Abstract: Persicaria stagnina (Hamilt. ex Maisn.) Hassan (Polygonaceae) is a perennial herb growing mostly in marshy areas, on the edges of ponds, ditches and other watery bodies. The plant is well-known and widely distributed in Bangladesh. Extracts of this plant and some of other Persicaria species are used as folk medicine by the native people. The piscicidal and molluscicidal activities of this plant and its content have recently been reported by Balze et al. (1). As a part of our work on the chemical constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…20b Polygodial inhibited an in vitro nematode larval motility assay against the sheep parasite Trichostrongylus colubriformis (IC 50 0.07 mg ml Ϫ1 ). 152 A mixture of 2,3-substituted alkoxycarbonyl isodrimeninols (46)(47)(48)(49) is used in Sudan as an anthelmintic agent. 48 Mukaadial and cinnamolide proved to be active when tested in vitro, using tissue cultures and in vivo using mice against Trypanosoma congolense, T. evansi and T. brucei.…”
Section: Piscicidal Molluscicidal and Anthelmintal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…20b Polygodial inhibited an in vitro nematode larval motility assay against the sheep parasite Trichostrongylus colubriformis (IC 50 0.07 mg ml Ϫ1 ). 152 A mixture of 2,3-substituted alkoxycarbonyl isodrimeninols (46)(47)(48)(49) is used in Sudan as an anthelmintic agent. 48 Mukaadial and cinnamolide proved to be active when tested in vitro, using tissue cultures and in vivo using mice against Trypanosoma congolense, T. evansi and T. brucei.…”
Section: Piscicidal Molluscicidal and Anthelmintal Activitymentioning
confidence: 99%
“…45 Polygonum hydropiper L is a very rich source of drimanes 46 and therefore other Polygonaceae, frequently used in folk medicine in different parts of the world, were also investigated including Polygonum punctatum, 47 P. glabrum, 48 and Persicaria stagnina. 49 Compounds belonging to the drimane group have been identified in certain tobaccos, where they are partly responsible for the characteristic flavour notes. 50a-c This is also the case in the essential oil from the rhizomes of Himalayan Hedychium acuminatum 51a and from Homalomena occulta.…”
mentioning
confidence: 99%
“…Arborinone (1) together with other arborane-type triterpenoids was found in the roots of P. bistorta (22), suggesting a close relationship between P. bistorta and P. sagittata. Meanwhile, steroids with stigmastane skeleton seem to accumulate in the aerial parts of P. barbata (23), P. ferruginea (24), and P. glabra (25), stems of P. chinensis (26) and P. pulchra (27), rhizomes of P. bistorta (20,22), and the whole plants of P. capi- (3) is a common steroid found in plants and it has been reported in the rhizome of P. bistorta (20) and the whole plants of P. nepalensis (21) and P. stagnina (29). On the other hand, 25-hydroxycholest-5-en-3β-yl acetate (2) and methyl-4-hydroxy cinnamate (4) were described for the first time in genus Persicaria that herein may enrich the chemotaxonomy aspect of this genus (Table 2).…”
Section: Chemotaxonomic Significancementioning
confidence: 99%
“…The crude fractions were subsequently separated and purified by repeated TLC to give about 200 mg stagninol. The compound under investigation was characterized and identified by comparing its Rf value and spectral data with those of reference compound (Ahmed et al, 1991).…”
Section: Isolation Of Stagninolmentioning
confidence: 99%
“…Chemical study on this plant has shown that it contains the hemiacetal type sesquiterpene stagninol, chemically being the 2α, 3β ditigloyloxy derivative of isodrimeninol (Fig. 1) (Ahmed et al, 1991). Pharmacological studies on this plant reveals the significant anti inflammatory, analgesic and diuretic activities (Ahmed et al, 1997).…”
Section: Introductionmentioning
confidence: 98%